An Integrated M-Tree Approach for Securing Information in Public Auditing Clouds - Anantharam, Banoth; Sharma, Rajesh; Rani, B. Kavitha (International Journal of Intelligent Systems and Applications in Engineering, 2023)
In cloud computing one of the most important components is “IAM”, Identity and Access management tool to decide the rights of an individual over a resource. The identity is a property, which contains most sensitive and vital information in the encrypted format. Access represents the parameters like viewing and types of actions that a user can perform on the data. In general, integrity of the data is provided by the Third-Party Auditor (TPA) by generating the hash values for the encrypted blocks. It takes lot of time to audit every encrypted block by the TPA, this increases the cost of deployment. The cloud resources to provide the access management to the resources either use the regenerating code whenever it is being shared with others or using the proxy server. The proxy servers suffer from “SSL stripping”, i.e., an attacker hacks the victim’s information by sending the https URL. The proposed research aims to solve this problem by enhancing the Merkle Trees technique in which the blocks are secured using the hashing functions. These hashing functions are generated by combining the properties of MD5 and SHA-256. The proposed research combined these two algorithms because while transferring the information the communications should be faster which is served by MD5 whereas security should not be breached, i.e., data should be encrypted in short and more secured format, this is achieved by SHA-256.